Kertomus postmodernismin jälkeen - Björninen, Samuli (Suomalaisen Kirjallisuuden Seuran Toimituksia, 2021)
Narrative After Postmodernism takes a critical and practical look at the cultural theories of what comes after postmodernism or the postmodern. Alongside contemporary literary authors, the anthology studies diverse contemporary textual phenomena from TV shows to online fan theories and survivalist blogs. The essays compiled in this anthology tentatively apply the theories of the post-postmodern to contemporary texts to see how they might open up for analysis within their new theoretical frameworks or challenge them.The introduction, co-written by all the authors of this volume, introduces the most influential theories of post-postmodernism and contextualizes them within broader intellectual trends of the early 21st Century. The three essays comprising the first part of the volume discuss some of the theories of the postmodern in relation to contemporary works that seem to challenge them. Yet they also strive to clarify and sharpen some of the ideas proposed in the theories of the post-postmodern.The second part of the volume aims to show that it is not only the contemporary texts that move beyond the postmodern - the ways of reading literature and interpreting artworks in different media are also changing. The essays in the second part of the volume inquire about the effects of the contemporary literary culture on the methods of interpretation and ways of reading.